Effect of Integrated Teaching on Students' Learning - Azadeh Ebrahimzadeh; Mohammad Reza Abedini; Kherionesa Ramazanzade; Bita Bijari; Hamed Aramjoo; Majid Zare Bidaki (Strides in Development of Medical Education, 2021)
Background: Currently medical education in Iran consists of basic sciences, physiopathology and clinical stages. Medical students learn them separately and often are confused that how basic sciences materials would be helpful for the patient’s diagnosis and treatment. Integration of various related subjects during medical education is one the proposed strategy to overcome this problem. Objectives: The present study was conducted to assess the effect of an integrated teaching approach on medical students’ attitudes and knowledge about infection diseases.Methods: This quasi-experimental study was conducted in the infectious disease ward of Valia-e-asr Hospital affiliated to Birjand University of Medical of Sciences, Birjand, Iran. A total of 60 medical students (stagers) were randomly selected and assigned to the control and intervention groups. The two groups were matched based on their grade point average (GPA), age, and gender. An integrated teaching approach was adopted in the intervention group by four epidemiology, microbiology, infectious diseases, and pharmacology professors. The students’ knowledge was assessed by a written exam, and their attitude was evaluated using a questionnaire. Data was analyzed by SPSS version 16 and using paired and independent samples t-test.Results: The analyses showed that 52% of the participants were male. The mean scores in the cognitive and emotional domains (the students’ points of view) were not correlated with students’ gender, and they were not significantly different before (p= 0.12) and after (p= 0.25) the intervention. The students’ final learning scores were significantly higher in the intervention group than that of the control group (16.16±1.17 vs 14.12±1.73; p=0.001).Conclusion: The integration of basic and clinical subjects helps students to better understand the physiopathology of diseases and enhances their satisfaction.